Washboarding: Are Man-Managed Honeybees Performing a Vestigial Activity Fostered by Cryptogams? - Giovanetti, Manuela; Máguas, Cristina; Munzi, Silvana (Journal of Apicultural Science, 2022)
A common view is that honeybees are mostly managed by beekeepers for commercial purposes or as a hobby, especially in Europe. This misconception is probably due to the lack of systematic studies on wild colonies of honeybees in Europe in comparison to other regions of the world. Since we are used to considering this species as “domesticated”, we may be induced to disregard activities not distinctly linked with colony survival, reproduction, or productivity. Washboarding is one of them in which the entire colony stops resource collection activities; numerous individual bees assemble on the front side of the hive and perform repetitive movements back and forth. They are curiously synchronised but apparently without a scope. In this exploratory work, we carried out a literature review of available, mostly grey, literature. Assuming this behaviour may be linked to cavity-nesting and to tree trunks or rocks being rough surfaces hosting various cryptogams, we performed preliminary observations and manipulative experiments. From our survey, we depict that washboarding is frequently reported in grey literature/beekeepers’ reports, but rarely mentioned in scientific literature. Beekeepers who responded to a designed questionnaire observed this behaviour in various ecological situations, with no trend emerging. Our preliminary experiment of placing cryptogams in front of managed hives resulted in honeybees removing lichens (foliose types) or covering with propolis, and all species were affected. Further research is needed to clarify if lichens are removed because of their chemical compounds, because of hosting potentially toxic microorganisms, or collected as resources.